2017
DOI: 10.1002/chem.201704369
|View full text |Cite
|
Sign up to set email alerts
|

Directed Self‐Assembly in “Breath Figure” Templating of Melamine‐Based Amphiphilic Copolymers: Effect of Hydrophilic End‐Chain on Honeycomb Film Formation and Wetting

Abstract: Amphiphilic copolymers are widely used in the fabrication of hierarchically honeycomb-structured films through a "breath figure" (BF) process because the hydrophilic block plays a key role in stabilising water templating. However, the hydrophilic monomers reported are mainly confined to acrylic acid and its derivatives, which largely limits understanding of the formation of BF arrays and the introduction of additional functions on porous films. The relationship between polymer composition, film microstructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The lateral capillary force and stable droplets are important factors that control the orderliness of the structure . Therefore, it is a good idea to choose polymers with special structural features, such as block copolymers, comb copolymers, and amphiphilic polymers, because their special structure makes them easier to self-assemble at the interface and prevent the coalescence of droplets. The addition of nanoparticles or surfactants as stabilizers could improve the stability of droplets to obtain high quality patterned films. It is difficult to develop ordered structures without adding nanoparticles or surfactants to nonpolar linear polymers, since the polymers cannot form envelopes and stabilize the droplets.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral capillary force and stable droplets are important factors that control the orderliness of the structure . Therefore, it is a good idea to choose polymers with special structural features, such as block copolymers, comb copolymers, and amphiphilic polymers, because their special structure makes them easier to self-assemble at the interface and prevent the coalescence of droplets. The addition of nanoparticles or surfactants as stabilizers could improve the stability of droplets to obtain high quality patterned films. It is difficult to develop ordered structures without adding nanoparticles or surfactants to nonpolar linear polymers, since the polymers cannot form envelopes and stabilize the droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian cell culture is a key technology to study animal physiological processes and to produce various biopharmaceuticals. It is well known that both the surface morphology and surface properties affect cell behavior. , Rough surfaces with ordered porous structures, that is, honeycomb-patterned PFs, are good substrates for cell attachment and spreading due to the significantly enlarged surface area and channels for cell–cell interaction. ,,, Previous studies ,,, revealed that honeycomb films with a hydrophilic surface can enhance the interaction between cells and films, leading to better performances for cell culturing. However, most honeycomb films prepared from pure polymers are normally hydrophobic due to the formation mechanism, ,,,, so that they are not suitable to be directly used as scaffolds. Additional treatment, such as UV irradiation, UV–ozone exposure, change of pH or change of temperature, ,,,, were applied to improve film surface wettability before cell culturing.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,12,45−48 Previous studies 25,35,49,50 revealed that honeycomb films with a hydrophilic surface can enhance the interaction between cells and films, leading to better performances for cell culturing. However, most honeycomb films prepared from pure polymers are normally hydrophobic due to the formation mechanism, 22,31,32,51,52 so that they are not suitable to be directly used as scaffolds. Additional treatment, such as UV irradiation, UV−ozone exposure, change of pH or change of temperature, 12,18,25,49,53 were applied to improve film surface wettability before cell culturing.…”
Section: Methodsmentioning
confidence: 99%
“…Surfaces patterned by BF mostly consist of polymers, copolymers, blends, or other soft matter compounds. ,, However, some reports show the development of hybrid materials using nanoparticles or metal ion precursors embedded in a high molecular weight polymer matrix. For instance, hybrid films for different functional applications have been prepared using Ag, , Au, Sn, or SiO 2 …”
Section: Introductionmentioning
confidence: 99%